Analyzing the environmental impact of copper-based mixed waste recycling-a LCA case study in China. (15th February 2021) - Zhang, Wenbiao; Li, Zehong; Dong, Suocheng; Qian, Peng; Ye, Shufeng; Hu, Shuhan; Xia, Bing; Wang, Chunying
Abstract: Copper-based mixed wastes include copper-containing wastes from the chemical, metallurgy, copper processing, printing, electronic component manufacturing, and other industries. Copper-based mixed wastes have high humidity and a significantly lower copper content than general waste copper, pose serious environmental hazards, and are very difficult to recover. The recycling of copper-based mixed wastes has important economic and environmental significance. Chinese companies have started extracting copper and other metals from copper-based waste mixtures and have achieved a high economic efficiency. This paper assesses the environmental impacts of copper-based mixed waste recycling and suggests possible optimization measures for the production process with respect to environmental impacts. The life cycle assessment (LCA) method is adopted to evaluate the effects of different production processes and to compare the environmental impacts of copper recovery from copper-based mixed waste recycling to the environmental impacts of primary and secondary copper production. Sensitivity analysis is conducted to estimate and evaluate the effects of possible production process optimization measures on environmental impacts. The results show the following: 1) The environmental impact of the copper-based mixed waste recovery process is generally superior to that of primary copper production in China on average, while it is inferior to that of secondary copper production. For example, the fossil energy consumption in primary copper production accounts for 74.9% of the impact of this process. 2) Smelting is the production process with the greatest environmental impact throughout the life cycle of copper-based mixed waste, accounting for 64.5% of the normalized index of the total environmental impact; and electrolysis and zinc recovery reach 19.8% and 12.1% of the total normalized index, respectively. 3) The raw materials and emission components with the largest environmental impacts are the carbon emissions from coal use and carbon dioxide emissions during smelting, the use of electricity during electrolysis, and the use of heavy oil and lime as raw materials during refining; these five items account for 69.7% of the total environmental impact. Thus, efforts at process improvement should focus on the full life cycle of energy utilization in the smelting process and on energy and material depletion in the refining and electrolysis processes. Specific process improvements and simulation analyses are important directions for further research. Highlights: The impact of the copper-based mixed waste recovery process is generally superior to that of primary copper production in China on average. Smelting is the production process with the greatest environmental impact. Five input-output items account for 69.7% of the total environmental impact.